2012
DOI: 10.1111/j.1460-9568.2012.08276.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of raphé serotonergic neural projections to the cortex: a potential pathway contributing to remote loss of brainstem neurons following neonatal hypoxic–ischemic brain injury

Abstract: Neuronal injury is a key feature of neonatal hypoxic-ischemic (HI) brain injury. However, the mechanisms underpinning neuronal losses, such as in the brainstem, are poorly understood. One possibility is that disrupted neural connections between the cortex and brainstem may compromise the survival of neuronal cell bodies in the brainstem. We investigated whether brainstem raphé serotonergic neurons that project to the cortex are lost after HI. We also tested if neuroinflammation has a role in disrupting brainst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
0
12
1
Order By: Relevance
“…Furthermore, inhibition of neuroinflammation in the forebrain but not in the brainstem reduces the HI-induced raphé 5-HT losses (23). 5-HT raphé fibers projecting to the forebrain but not fibers that project to the medulla and the spinal cord (fibers from the raphé magnus, palidus, and obscurus) are disrupted after HI (6,24). We then proposed that the release of 5-HT in the medulla and the spinal cord might be affected since the 5-HT contents were modified in these regions after HI.…”
Section: Possible Brainstem Dysfunctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, inhibition of neuroinflammation in the forebrain but not in the brainstem reduces the HI-induced raphé 5-HT losses (23). 5-HT raphé fibers projecting to the forebrain but not fibers that project to the medulla and the spinal cord (fibers from the raphé magnus, palidus, and obscurus) are disrupted after HI (6,24). We then proposed that the release of 5-HT in the medulla and the spinal cord might be affected since the 5-HT contents were modified in these regions after HI.…”
Section: Possible Brainstem Dysfunctionsmentioning
confidence: 99%
“…has been extensively used to investigate cognitive and sensorimotor functions; however, it should be emphasized that depending on the age of the insult, the results should be cautiously discussed. Previous studies interested in the 5-HT systems have used the rat model at P3 (6). Although still debated, P7 as corresponds to a brain development of 34-36 wk gestational age in the human fetus (10,33).…”
Section: Animal Model and Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…In a neonatal rat model, Reinebrant et al demonstrated that disrupted serotonergic inputs to the motor cortex resulted in brainstem serotonergic neuronal loss after hypoxic-ischemic injury. [42] Disruption of the brainstem and spinal cord serotonergic system has also been proposed to account for the motor defects observed in neonatal mice using the Rice– Vanucci hypoxic-ischemic injury model. [43] Future studies in our UCO model investigating damaged neural pathways, such as serotonergic system pathway, after neonatal HIE may reveal cellular mechanisms of axonal degeneration relevant to the development of CP.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment trials in both animal models and human patients have been carried out for a number of neurodegenerative diseases, including multiple sclerosis, spinal cord injury, amyotrophic lateral sclerosis, Huntington disease, Parkinson disease and Alzheimer disease, with encouraging results in a number of cases. For example, recent rodent model trials have indicated efficacy against hypoxic-ischemic brain injury [23], blast-induced traumatic brain injury [24], Alzheimer disease-like amyloid pathology [25] and Huntington disease-like symptoms [26]. However, results from rodent model studies have not been very good indicators of human studies, indicating that larger animal models would be preferred, and there have also been some concerns about chronic treatment in some cases [20,21].…”
Section: Introductionmentioning
confidence: 99%